Impact of Transition Metal Layer Vacancy on the Structure and Performance of P2 Type Layered Sodium Cathode Material (vol 16, 239, 2024) - Zhanadilov, Orynbay; Baiju, Sourav; Voronina, Natalia; Yu, Jun Ho; Kim, A-Yeon; Jung, Hun-Gi; Ihm, Kyuwook; Guillon, Olivier; Kaghazchi, Payam; Myung, Seung-Taek (Shanghai Jiao Tong University Press, 2024)
Following publication of the original article [1], the authors reported that the author Hun-Gi Jung should be affiliated as 3, 4 and 5 instead of 4 and 5. The author's name “A.-Yeon Kim” needed to be updated to “A-Yeon Kim”, removing the period. The correct author’s name and affiliation have been provided in this Correction. The original article [1] has been corrected.